2014 American Control Conference 2014
DOI: 10.1109/acc.2014.6859476
|View full text |Cite
|
Sign up to set email alerts
|

A robust hybrid control algorithm for a single-phase DC/AC inverter with variable input voltage

Abstract: In this paper, we analyze the properties of the vector fields associated with all possible configurations of a single-phase DC/AC inverter with the objective of designing a hybrid controller for the generation of an approximation of a sinusoidal reference signal. Using forward invariance tools for general hybrid systems, a hybrid controller is designed for the switched differential equations capturing the dynamics of the DC/AC inverter. Then, global asymptotic stability of a set of points nearby the reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Then, we may model the system as in [4]: where V DC is the input DC voltage and R, L, C are parameters of the circuit. As mentioned in Section I, a PWM-based controller switches among some of these configurations depending on the difference between a reference carrier and a modulating signal.…”
Section: Analytical Model Of a Single-phase Dc/ac Invertermentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we may model the system as in [4]: where V DC is the input DC voltage and R, L, C are parameters of the circuit. As mentioned in Section I, a PWM-based controller switches among some of these configurations depending on the difference between a reference carrier and a modulating signal.…”
Section: Analytical Model Of a Single-phase Dc/ac Invertermentioning
confidence: 99%
“…This approach is inspired by the work in [4] and provides an alternative to traditional PWM-based controls. The general idea behind the proposed approach is to generate an AC voltage at the output of the inverter circuit by tracking a sinusoidal reference signal.…”
Section: Hybrid Predictive Control For the Tracking Of A Sinusoimentioning
confidence: 99%
“…We devote this section to present an application for the proposed forward invariance analysis tools in this work. The system of interest is a controlled single-phase DC/AC inverter; see [35] for complete design details. As shown in Fig.…”
Section: Forward Invariance Analysis For a Controlled Single-phase DCmentioning
confidence: 99%
“…Then, for every x ∈ ∂T \ L, by applying Lemma .5 and the inner product properties listed in [35,Lemma 2], we have the value of q chosen by the designed controller always results in one of the two cases below:…”
Section: Forward Invariance Analysis For a Controlled Single-phase DCmentioning
confidence: 99%
“…Relying on forward invariance results, invariance-based control design techniques are widely used tools for controller design for systems with inputs. For example, invariancebased control designs are provided in [5] for power inversion, in [6] for a genetic network, and in [7] for collision avoidance in automotive systems. While tools for the study of forward invariance and viability in hybrid systems can be found in [8], [9], [10], to the best of our knowledge, results enabling the systematic design of feedback controllers inducing forward invariance for hybrid systems are not available.…”
Section: Introductionmentioning
confidence: 99%